Electronic Study Guides for Applied Bachelor’s Degree Programs - D. V. Maltsev; E. M. Genson; D. S. Repetskiy (Высшее образование в России, 2019)
The development of electronic study guides (ESG) for Bachelor’s disciplines enables to reduce procurement costs for print library collections. Posting of ESGs on the University Internet resources will provide their accessibility and usability, so the subject is topical. The article analyzes the experience of developing electronic study guides for the disciplines of basic professional bachelor’s degree programs in various universities and reviews the literature on this subject. The main features that distinguish ESG from paper teaching materials are the following: multimedia presentation of information, interactivity, dynamic content. In addition, remote interaction between a teacher and students in forums or video conferences is possible, depending on the format of the ESG. Furthermore, ESG allows one to remotely monitor the completeness and timeliness of the study of certain topics of the discipline, unlike other types of educational and methodological support. The implementation of the ESG makes it possible to maintain control in two forms: internal and external. There are also such criteria for assessing the quality of ESG as: proportion in ensuring the total volume of discipline, proportion in ensuring the self-directed student work, quality of design, the effectiveness of multimedia, adaptability, level of remote access. The result of the analysis was the development of requirements for the ESG design for the discipline «Structure and calculation of engines». This discipline includes the basics of structure and calculation elements and systems of internal combustion engines and the processes occurring in them. In Perm National Research Polytechnic University, according to the curriculum, the discipline is studied for 2 semesters; the labor intensity is 7 credits. Classroom lessons consist of lectures, laboratory and practical classes, additionally, coursework was provided. The difficulty of organizing and maintaining a laboratory in working condition is due to high labor and material costs for fuels and lubricants, electricity, forced-air ventilation, maintenance and repair of internal combustion engines, etc. In this regard, it is relevant to use simulation methods and create virtual laboratory benches to determine the characteristics of the internal combustion engine. These benches may be considered as an alternative to field experiments and stands. As a result of the generalization experience, it was possible to draw up general requirements to the structure and content of the ESG and to provide recommendations on the development of ESGs taking into account the specifics of applied bachelor’s programs.